FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN ASUHAN KEPERAWATAN DI RS GRANDMED TAHUN 2020 - Juni Mariati Simarmata; Beti Susanti Tarigan; Dian Anggriyanti; Syatria Wati; Rosita Ginting; Pratiwi Christa Simarmata; Pitriani . (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Nursing care services certainly cannot be separated from the nursing process, starting from nursing assessments, nursing diagnoses, nursing interventions, nursing implementation, evaluation and documentation. There are several factors related to the implementation of nursing care at Rs GrandMed Lubuk Pakam in 2020. This study used an analytical survey research with a cross sectional study approach. The population in this study were all employees of 3 Depan. The sample in this study was used as many as 12 respondents according to the inclusion criteria. The results of this study indicate that, there is no relationship between nurse education and the implementation of nursing care (p = 1), there is no relationship between the work tenure of nurses and the implementation of nursing care (p = 0.293), there is a relationship between the workload of nurses and the implementation of nursing care (p = 0.293). p = 0.010), There is a relationship between incentives and the implementation of nursing care (p = 0.010), There is a relationship between work atmosphere and the implementation of nursing care (p = 0.045), There is a relationship between leadership style and the implementation of nursing care (p = 0.045). So it can be concluded that there is a relationship between workload, incentives, work atmosphere and leadership style on the implementation of nursing care.